APPROACHES TO THE STUDY OF MATERIALS ON THE NORTH CAUCASUS IN THE JOURNAL «OTECHESTVENNYE ZAPISKI»: THE METHOD OF JACQUES KAISER - P. A. KUZ’MINOV; I. S. TAKHUSHEVA (Кавказология, 2020)
The article discusses two key problems of modern Caucasian studies. Firstly, the question of representing the history of the peoples of the North Caucasus in the liberal-democratic press of Russia in the 19th century is analyzed. The journalistic activities of the editorial board of the «Otechestvennye zapiski» contributed not only to the collection, analysis and broadcast of relevant information about the daily life of the mountaineers of the Caucasus, their traditions and customs, mental characteristics, government policies in the region, forms and methods of integrating the Caucasus into Russia, but also helped to preserve historical sources. The need to expand the source base on the history of the mountaineers of the Caucasus requires a wider inclusion of articles from pre-revolutionary journals in the research practices of historians and historiographers of the North Caucasus. Secondly, the effectiveness of using the methodological approach of the French scientist Jacques Kaiser in the study of press materials in Caucasian studies is substantiated. The theoretical and methodological construction of J. Kaiser, based on filling out «signal cards» for periodicals, compiling a research «dossier» for publishing and revealing the «morphology» of the journal, allowed not only to study the leading liberal-democratic press organ of Russia, starting with its external characteristics to the conceptual views of the editors, but also to find out the reasons for broadcasting information about the peoples of the North Caucasus, the qualitative content of these articles, as well as original ways of submitting and ranking the materials series about the mountaineers of the Caucasus on the pages of the «Otechestvennye zapiski».